The challenges of child bullying and its prevention in islamic elementary schools - Umu Miftahur Rohmah; Syamsul Arifin; Lilis Sumaryanti; Sigit Dwi Laksana; Ayok Ariyanto (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study discusses bullying which focuses on the objectives, methods and findings obtained. The main objective of this study was to understand the challenges of bullying and its coping strategies. The method used in this study includes a qualitative approach with data collection through observation, interviews and documentation. The validity test of the data in this study used the triangulation technique. The results of the study show that bullying has a negative influence on the micro and macro social scales, both between perpetrators and victims. These findings provide new insights into the challenges of bullying and how to develop more effective prevention and handling strategies. This applies mainly to parents and teachers who are fully supported by the community and the government.